Surgical drains following arthroplasty: a systematic review and summary of evidence based on available systematic reviews - Singapanga, Rupin S.; Ahmed, Rayeez; Samuel, Ajay N. (International Journal of Research in Orthopaedics, 2025)
The use of surgical drains following arthroplasty is an age-old practice, but has declined in popularity in recent times. Various aspects pertaining to their safety and efficacy have been studied in the past, in focused studies and systematic reviews. The present research aimed to review and summarize the high-quality evidence on the subject. A described methodological framework for conducting a “systematic review of systematic reviews” was chosen, and reporting was performed in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Following a search in the PubMed/Medline and PubMed Central indexing databases, a total of 34 systematic reviews with or without meta-analyses were included. Our research unequivocally indicates that routine drain application is not associated with a reduction in the incidence of postoperative hematoma formation or limb swelling, though it unambiguously results in a significant reduction in the incidence of surgical site erythema and ecchymoses, and the need to change wound dressings postoperatively. This benefit, however, comes at the expense of the possibility of increased blood loss, transfusion requirement, and time to functional recovery, as well as the deterrence to a full implementation of the principles of “enhanced recovery after surgery” protocols and day-care surgery. Where drains are deemed inevitable, the practice of intermittent clamping can mitigate the magnitude of blood loss, while autologous re-transfusion drains may reduce blood transfusion requirements.